Integrating mass spectrometry with MD simulations reveals the role of lipids in Na+/H+ antiporters - Michael Landreh (Nature Portfolio, 2017)
Na+/H+antiporters transport sodium or lithium ions across the membrane in exchange for protons. Here the authors combine ion mobility mass spectrometry and molecular dynamics simulations to uncover a facilitating role for lipids in the transport mechanism.